1911 Relay Team C.P.S - Frank Aston::::::photographer::: (1911)
Relay team in uniform on track; buggy in background; Team members identified on back of postcard; 'Leona Forbes, May 1911' also written on card. Leona Forbes [Stenner] graduated in 1913.